Characteristics of CO2 Capture using Biphasic Absorbent by AMP/DEGDEE/H2O - MACHIDA, Hiroshi; SUGAI, Yuichi; ESAKI, Takehiro (Journal of MMIJ, 2024)
We evaluated the absorption characteristics and phase state of a biphasic CO2 absorbent using 2-amino-2-methyl-1-propanol (AMP), diethylene glycol diethyl ether (DEGDEE), and water (H2O). We set the AMP concentration at 30 wt%, and adjusted the H2O and DEGDEE weight fractions. It was experimentally confirmed that phase separation of the absorbents occurred due to the progress of CO2 absorption. As the concentration of water decreased, it was separated into a lower phase, which consisted almost entirely of AMP, H2O and absorbed CO2, and an upper phase, which consisted of mostly DEGDEE. In the experiment, an absorbent composition of 30 : 20 : 50 wt.% (AMP:DEGDEE : H2O) was maintained in the liquid state at 313 K and a CO2 partial pressure of 0.1 atm in the absorption step and at ≥ 343 K and a CO2 partial pressure of 1.0 atm in the regeneration step. Under CO2 capture conditions, this adsorbent was separated into two-liquid states in the absorption step, whereas it exhibited a uniform single phase in the regeneration step. Therefore, it could operate under CO2 capture conditions as a biphasic absorbent. The amount of CO2 cyclic absorption of this absorbent was twice that of conventional monoethanolamine (MEA) absorbents when the regeneration temperature was set at 363 K.